(untitled) (Herald of the National Children’s Medical Center, 2025)
Ensuring adequacy and safety of anesthetic management in pediatric ophthalmology requires an individualized approach and a high level of monitoring, due to the anatomical and physiological characteristics of pediatric patients and specific risks, including the oculocardiac reflex. The latter is a potentially dangerous complication during interventions on the eyeball and requires effective prevention. Modern strategies, including multimodal analgesia and gentle sedation, help minimize risks and improve outcomes.